The Influence of Service Customization and Interactive Tour Guides on Foreign Tourists' Willingness to Pay at Bali Tourist Destinations - Novitasari, Salwa Aulia; Suharto, Bambang; Priyana, Yana (West Science Interdisciplinary Studies, 2025)
This study investigates the effect of service adjustments and interactive tour guides on foreign tourists’ willingness to pay at Bali tourist destinations. The research adopts a quantitative approach using a sample of 150 foreign tourists selected through purposive sampling. Data were collected via structured questionnaires measured with a five-point Likert scale and analyzed using SPSS version 25. Statistical techniques included descriptive analysis, validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The findings reveal that both service adjustments and interactive tour guides have significant and positive effects on foreign tourists’ willingness to pay. The regression model shows that these two variables collectively explain 62.1% of the variation in tourists’ willingness to pay. Service adjustments—such as cultural sensitivity, language flexibility, and personalized itineraries—enhance perceived value, while interactive guides contribute to emotional engagement and trust, thereby increasing payment intention. The study provides theoretical contributions by integrating service quality theory, customer value theory, and social exchange theory in explaining tourists’ economic behavior. Practically, it offers strategic insights for tour operators and policymakers to enhance adaptive and interactive service quality to strengthen Bali’s tourism competitiveness and sustainability.